Metadata In, Library Out. A Simple, Robust Digital Library System - Tonio Loewald; Jody DeRidder (Code4Lib Journal, 2010)
Tired of being held hostage to expensive systems that did not meet our needs, the University of Alabama Libraries developed an XML schema-agnostic, light-weight digital library delivery system based on the principles of "Keep It Simple, Stupid!" Metadata and derivatives reside in openly accessible web directories, which support the development of web agents and new usability software, as well as modification and complete retrieval at any time. The file name structure is echoed in the file system structure, enabling the delivery software to make inferences about relationships, sequencing, and complex object structure without having to encapsulate files in complex metadata schemas. The web delivery system, Acumen, is built of PHP, JSON, JavaScript and HTML5, using MySQL to support fielded searching. Recognizing that spreadsheets are more user-friendly than XML, an accompanying widget, Archivists Utility, transforms spreadsheets into MODS based on rules selected by the user. Acumen, Archivists Utility, and all supporting software scripts will be made available as open source.